The Association Between the Severity of Diabetic Peripheral Neuropathy and Diabetic Risk Factors in Diabetic Patients Type I and II. - Sarah Ali Alkindy (Journal of Global Pharma Technology, 2016)
Back ground: The diabetic risk factors can effect on the severity of diabetic peripheral neuropathy (DPN). The most risk factors have an effect on the peripheral nervous system are duration of diabetic disease, glycocelated hemoglobin (HbA1C) and type of diabetes (DM type). Objectives: To determine the association between severity of DPN and duration of diabetes, HbA1C, the type of diabetes, age and sex of diabetic type I and II patients. Patients and Methods: Three hundred individuals were participated in cross sectional study. They divided to two groups labeled as A and B. Group A regarded as diabetic patients with abnormal neurological examination. Group B regarded as diabetic patients with normal neurological examination. About 68 male and 82 female were participated in this study for each group.  The age of participant are grouped as <18, 18-30 and 31-60 year. The full history was taking from participants including socio demographic data and duration of disease with type of diabetes. All participants with type I and II underwent clinical assessment and biochemical investigation. The clinical assessment used Toronto clinical scoring system (TCSS) for screening diabetic peripheral neuropathy (DPN). The biochemical investigation was done for determining the level of HbA1C. The study was carried out at Marjan teaching hospital and Al Sadeq teaching hospital in Babylon province during the period from Aug.2017 to Sep.2018.Results:TCSS used for scoring the DPN to mild, moderate and severe. The severity of DPN show significant association with duration of DM disease,  type of diabetes , the level of HbA1C and age of diabetic patients, the P value about o.oo1, 0.02 , 0.001 and 0.001respectively. The sex of  diabetic patients showed no significant association with severity of DPN, the P value 0.45.Conclusions: There is higly association between severity of DPN and DM duration, HbA1C , type of DM and age of diabetic patients. There is no association between sex of diabetic patients and severity of DPN.